Implementasi Pembelajaran Flipped Classroom pada Pendidikan Pancasila untuk Meningkatkan Civic Engagement di Salah Satu SMA Muhammadiyah Klaten - Salma Alya Fadhilah; Obby Taufik Hidayat (Universitas Muhammadiyah Ponorogo, 2026)
This study aims to examine the implementation of the flipped classroom learning model in Pancasila Education and students' learning experiences through the model in enhancing civic engagement at SMA Muhammadiyah Klaten. The main problem underlying this research is the dominance of conventional teacher-centered learning which inhibits students' active participation and civic involvement. This study employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation. The findings indicate that the implementation of flipped classroom through the stages of planning, execution, and evaluation successfully shifted the learning paradigm toward student-centered learning. Students experienced positive changes cognitively, affectively, and socially, marked by increased learning independence, courage in expressing opinions, collaborative skills, social awareness, and digital literacy as a form of civic participation. This study concludes that flipped classroom is proven effective not only in improving content understanding but also in genuinely cultivating students' civic engagement values within the context of Pancasila Education.